Peranan Perempuan Single Mother Dalam Keluarga Miskin di Jorong Balai Mansiro Nagari Guguak Viii Koto - Jasmienti Jasmienti; Nofrianti Putri Utami (HUMANISMA : Journal of Gender Studies, 2019)
This study aims to determine the role of a single mothers in poor families. This research used qualitative research. The method of collecting data was by interviewing several informants and observing some single mothers. An interesting phenomenon in poor families was in sustaining life with a decent standard of living, firstly on saving the expenditure side, postpone the expenses related to transportation. Second, the income of households, poor households forced them to optimize their income through the mobilization of their economic resources. This effort is carried out to be able to maintain a level of welfare or a decent life. However, not all of these efforts are able to maintain a decent level of life.